Restoration of Degraded Desert Pastures - Haydarov Hasanjon Hakimovich; Kushimov Bakhtiyor Alishovich (Academia One, 2023)
This scientific article aims to explore the restoration of declined desert pastures. The study utilizes a literature analysis and methodology to assess the current state of desert pastures and identify effective restoration strategies. The results indicate that several approaches, such as soil improvement techniques, water management, and reseeding, can contribute to the restoration of declined desert pastures. The discussion highlights the importance of ecosystem resilience and emphasizes the need for sustainable land management practices. Overall, this study provides valuable insights into the restoration of desert pastures and offers recommendations for future restoration efforts.
Keywords: Desert pastures; restoration; decline; soil improvement